2010
DOI: 10.1038/onc.2010.72
|View full text |Cite
|
Sign up to set email alerts
|

EWS/ETS proteins promote expression and regulate function of the homeodomain transcription factor BRN3A

Abstract: Ewing's sarcoma family tumors (ESFTs or EFTs) express neuronal markers, which indicates they may originate from cells at least partly committed to neuronal lineage. However, recent publications suggest EFT originates in mesenchymal stem cells, and EWS/ETS fusion proteins characteristic of EFT activate neuronal marker expression to confer a neural phenotype on EFT. Here we show that the neuronal marker BRN3A/POU4F1 is expressed abundantly at the protein level in primary EFT but not in rhabdomyosarcoma and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…In 2010 [104] Gayscone reported that the neuronal marker BRN3A is expressed abundantly at the protein level in primary ESFT but not in neuroblastoma or rhabdomyosarcoma. Therefore, it appears that EWS/ETS proteins induce expression of neuronal markers and stimulate early stages of neuronal development but prevent terminal neuronal differentiation.…”
Section: Ontogenesis Of Esftmentioning
confidence: 99%
“…In 2010 [104] Gayscone reported that the neuronal marker BRN3A is expressed abundantly at the protein level in primary ESFT but not in neuroblastoma or rhabdomyosarcoma. Therefore, it appears that EWS/ETS proteins induce expression of neuronal markers and stimulate early stages of neuronal development but prevent terminal neuronal differentiation.…”
Section: Ontogenesis Of Esftmentioning
confidence: 99%